EVALUASI KEKUATAN STRUKTUR BAJA BERGELOMBANG BERDASARKAN TIPE DAN KETEBALAN - Hardiansyah Putra (Direktorat Bina Teknik Jalan dan Jembatan, 2019)
ABSTRACT There are three types of corrugated steel structure material, standard, deep and superdeeep. These three types are distinguished by the cross-sectional dimension so that there are differences in the value of moment inertia, the greater value of moment inertia it will make maximum span can be wider. In Indonesia, this construction material has been used as a bridge structure. The assessment of the strength of corrugated steel structure seen from three criteria there are, compression failure, plastic hinge, and connection failure. In the planning stage iteration of calculations is needed to get the optimum selection of type and thickness, so calculation and analysis is carried out on a 15-meter wide span with a semicircular construction in order to know the percentage increase in strength of each type change and thickness of steel used. The method of calculation is based on guidelines issued by the Canadian Highway Bridge Designs Code. Based on the calculation results, the greater of moment Inertia will increase the strength of the corrugated steel structure. Evaluation results show that the average strength increase of 3 viewing paremeters for each type and thickness of steel is, for the standard type average value of wall strength compression increasses by 9%, the average of seam strength increases by 3 % and the average of plastic hinge increases by 11%. For deep type, average value of wall strength compression increasses by 24%, the average of seam strength increases by 25 % and the average of plastic hinge increases by 19%. For superdeep type, average value of wall strength compression increasses by 41%, the average of seam strength increases by 27% and the average of plastic hinge increases by 34%. These results show highest incresaing of strength happen in superdeep type. Keyword: corrugated steel strcucture, inersia moment, wall strength compression, seam strength, plastic hinge.